Personal, Product, Service, and Technology: Key Factors of Purchase Behavior - Villan, Irish Grace; Dagang, Anthony Ly (Journal of Interdisciplinary Perspectives, 2025)
The rapid growth of food delivery applications (FDAs) has reshaped consumer purchasing behavior, especially in urban settings. This study explored the influence of personal, product and service, and technology-related factors on purchase behavior among FDA users. Grounded in the Theory of Planned Behavior, the Technology Acceptance Model, and Grönroos’ Service Quality Theory, the research surveyed 223 teaching and non-teaching employees from a higher education institution in Cagayan de Oro City, Philippines. Key variables examined include attitude toward the use of FDAs, perceived behavioral control, product presentation, delivery, customer support, return and exchange, benefits, and perceived ease of use. Utilizing a descriptive correlational research design, a validated structured questionnaire, and random sampling, data were gathered and analyzed using descriptive statistics and multiple regression. Among the independent variables, attitude towards the use of the FDA, return and exchange, perceived ease of use, and delivery significantly influence purchase behavior. Personal factors, product and service factors, and perceived ease of use were consistently rated high. However, purchase behavior measured in terms of frequency, quantity, and repurchase intention was at a moderate level. Notably, delivery showed a negative relationship, suggesting that users may tolerate delivery issues and continue using FDAs, reflecting an adaptive mindset. Entrepreneurs are encouraged to improve consumer attitudes through campaigns focused on convenience and consistent service, and to implement clear return policies. Future research may consider additional variables such as trust and social influence, or explore more diverse participant groups.